Implementation of multi-UAV communication relay function based on mobile telecommunication technology - Wen-Chung Tsai; Nien-Ting Huang (EURASIP Journal on Wireless Communications and Networking)
Abstract This paper presents a Medium Access Control (MAC) functionality design for Unmanned Aerial Vehicle (UAV) relay transmission. In contrast to existing relay designs, this work proposes a relay transmission framework based on 3GPP communication protocols. The core innovation lies in the introduction of an internal link channel within the Layer-2 MAC, enabling integration of Base Station (BS) and User Equipment (UE) functionalities within a single UAV communication module. The proposed Layer-2 MAC design is implemented within a System on a Programmable Chip, integrating both BS and UE functionalities into a unified platform. This modular approach allows future updates to BS and UE designs in line with evolving 3GPP standards by modifying only the relevant Intellectual Property (IP) components. Consequently, UAVs can efficiently support new communication standards while leveraging the reliability and stability of commercially validated mobile communication technologies. The proposed design methodology capitalizes on mature mobile telecommunication frameworks to achieve high data throughput and low latency, ensuring real-time and reliable UAV communication. This paper details the relay transmission architecture, platform implementation, and simulation environment, presenting experimental results that evaluate relay functionality and priority-based transmission performance.